SISTEM INFORMASI GEOGRAFIS UNTUK PERJALANAN WISATA DI KOTA SEMARANG - Manongga, Danny; Papilaya, Samuel; Pandie, Selfiana (Jurnal Informatika, 2009)
Tourist information system is an information system which built to fulfil the needs of information from tourists. This kind of information can be split into three major phases: pre-visiting information (before the trip), in site information and post-visiting (after the trip) information. A good tourist information system should support all of this phase. But in this case, the system will more concern to the second phase. In the second phase, the tourist already has a plan, what he wants to see, and what he wants to do and knows all the information required. Information from a guide book or map will help them find a location of a place or which way they should take and help them figured out the location of the places. To provide this kind of information, geographic information system (GIS) seems to be a good tool to handle this problem. GIS has capability to provide information and deliver them as guidance to user in a map form. The map consists of some space data and description about that space data. GIS could provide information such as a map of the important places like hotel, restaurant, tourist site, bank and the others, and about the street that pass all the places and providing some description about the places or street. This system will be applied to Semarang, with the searching tool as a major tools and information about all the tourism facilities in Semarang provided for the tourist with some pictures of them. With all the capability of GIS may tourist could have some guidance to help them along their trip in Semarang. Abstract in Bahasa Indonesia: Sistem informasi wisata adalah sistem informasi yang dibangun untuk memenuhi kebutuhan informasi wisatawan. Informasi dibedakan menjadi tiga bagian yaitu informasi sebelum perjalanan, informasi saat perjalanan dan informasi setelah perjalanan. Sebuah sistem informasi wisata yang baik harus dapat menyediakan informasi dari keseluruhan bagian tersebut. Penelitian ini menekankan pada bagian yang kedua. Dalam bagian kedua ini, wisatawan telah merencanakan perjalanan, tempat yang dikunjungi, apa yang ingin dilakukan, dan informasi yang ingin diperoleh. Informasi dari buku panduan dan peta membantu pencarian lokasi atau rute yang perlu ditempuh dan membantu mencari lokasi. Untuk penyediaan informasi, Sistem Informasi Geografis (SIG) merupakan alat bantu yang tepat untuk menangani masalah ini. SIG memiliki kemampuan untuk menyediakan informasi dan menampilkan dalam bentuk peta. Peta terdiri dari data dan deskripsi tentang data. SIG dapat menyediakan informasi seperti hotel, restoran, tempat wisata, bank dan lainnya, jalan yang menghubungkan tempat-tempat tersebut, maupun deskripsi tentang tempat dan jalan. Sistem diimplementasikan di kota Semarang, dengan menyediakan tools untuk searching dan informasi tentang fasilitas wisata beserta foto untuk wisatawan. Dengan kemampuan SIG, wisatawan mempunyai panduan untuk membantu perjalanan di Semarang. Kata kunci: perjalanan wisata, Sistem Informasi Geografis (SIG), Semarang